Intracellular phosphate homeostasis – A short way from metabolism to signaling. (September 2019) - Fabiańska, Izabela; Bucher, Marcel; Häusler, Rainer E.
Highlights: Phosphorus, an essential macronutrient for plant growth and development, is taken up from the rhizosphere in form of inorganic phosphate (Pi). Five families of phosphate transporter proteins (PHTs) facilitate uptake of Pi from soil and its allocation to below- and above-ground organs. PHTs also mediate the subcellular Pi distribution between various organelles of a cell, like plastids, mitochondria, vacuoles, or golgi. The orchestration of PHT and plastidial phosphate translocator (PT) activities enables maintenance of cellular/subcellular Pi homeostasis. Besides their role in metabolism, PHTs and PTs may contribute to signaling processes in sensory plastids of the vasculature. Abstract: Phosphorus in plant cells occurs in inorganic form as both ortho- and pyrophosphate or bound to organic compounds, like e.g., nucleotides, phosphorylated metabolites, phospholipids, phosphorylated proteins, or phytate as P storage in the vacuoles of seeds. Individual compartments of the cell are surrounded by membranes that are selective barriers to avoid uncontrolled solute exchange. A controlled exchange of phosphate or phosphorylated metabolites is accomplished by specific phosphate transporters (PHTs) and the plastidial phosphate translocator family (PTs) of the inner envelope membrane. Plastids, in particular chloroplasts, are the site of various anabolic sequences of enzyme-catalyzed reactions. Apart from their role in metabolism PHTs and PTs are presumed to be also involved in communication between organelles and plant organs. Here we will focus on the integration of phosphate transport and homeostasis in signaling processes. Recent developments in this field will be critically assessed and potential future developments discussed. In particular, the occurrence of various plastid types in one organ ( i.e. the leaf) with different functions with respect to metabolism or sensing, as has been documented recently following a tissue-specific proteomics approach (Beltran et al., 2018), will shed new light on functional aspects of phosphate homeostasis.